Metaanalisis Efek Pendekatan STEM pada Literasi Sains dan Pemahaman Konsep Peserta Didik di Setiap Satuan Pendidikan - Rima Melani Putri*; Asrizal Asrizal; Usmeldi Usmeldi (Universitas Syiah Kuala, 2022)
The competience of 21st century emphasizes to the skills, attitudes and knowledge. literacy skills and mastery of concepts are needed in facing the challenges of the 21st century. Currently, students' scientific literacy skills and mastery of concepts are relatively low. This happens because of the lack of a learning approach that includes scientific literacy. Therefore, in this study, an analysis of the effect of the stem approach on scientific literacy and students' mastery of concepts was carried out. The sample use is 20 journals that have met the criteria. The data analysis technique is the calculation of the effect size of each journal. Based on the results of the study, it can be concluded that the stem approach has a significants influence at every level of education an every grade level, both elementary and junior high schools in improving science prosess skills and student achievement